Visual response and anatomical changes on sequential spectral-domain optical coherence tomography in birdshot chorioretinopathy treated with local corticosteroid therapy. Issue 1 (December 2016) - Gobuty, Marisa; Adhi, Mehreen; Read, Sarah; Duker, Jay
Abstract Background Birdshot chorioretinopathy is a chronic bilateral inflammatory disease of unknown etiology characterized by bilateral retinal vasculitis, mild to moderate vitritis, retinal vascular leakage, cystoid macular edema (CME), and typical "birdshot" chorioretinal lesions. Typically, patients with birdshot chorioretinopathy are treated with systemic immunosuppressive and/or corticosteroid therapy in an effort to minimize loss of vision. Spectral-domain OCT (SD-OCT) has shown regional or generalized photoreceptor loss in addition to both retinal as well as choroidal thinning in these patients. The present study describes anatomical changes of the retina and alterations in choroidal thickness and vasculature on sequential spectral-domain optical coherence tomography (SD-OCT) in 4 patients with birdshot chorioretinopathy treated with local corticosteroids. Methods A retrospective observational case series identified 4 consecutive patients (8 eyes) at New England Eye Center, Boston diagnosed with birdshot chorioretinopathy according to the research criteria of the international consensus conference that were managed by a single retina specialist and treated exclusively with local corticosteroid therapy (intravitreal/sub-tenon injections) without systemic immunosuppression. All patients underwent longitudinal SD-OCT imaging with both the 512 × 128 cube scan and the 1-line raster protocol. A chart review was performed to review the visual response to treatment. Two independent observers analyzed sequential SD-OCT images for retinal parameters such as occurrence of CME at any time during the course of disease, presence of retinal thinning and presence of hyper-reflective foci within the retina, and choroidal parameters including its thickness and its vasculature. Results Mean age of the patients at diagnosis was 47 years (26–60 years). Mean duration of follow-up was 96 months. All patients were HLA-A29 positive. Visual acuity remained stable in 75 % of eyes, 63 % eyes had central retinal thinning, 75 % eyes had hyper reflective foci within the retina and 75 % eyes had CME during follow-up. Mean total sub-foveal choroidal thickness of all 8 eyes at the time of the last SD-OCT was significantly lower than at initial SD-OCT (p = 0.03). Conclusions This case series suggests that treatment with local corticosteroids may have good visual outcome despite retinal and choroidal thinning. Future longitudinal studies are necessary to further determine the benefits of local corticosteroid therapy.